Experimental and DEM simulation of sandy soil reinforced with H–V inclusions in plane strain tests. Issue 3 (1st June 2013) - Lin, Y.L.; Zhang, M.X.; Javadi, A.A.; Zhang, S.L.; Lu, Y.
Abstract : ABSTRACT: Horizontal–vertical (H–V) reinforcing elements are a new type of soil reinforcement in geotechnical engineering. The advantages of this reinforcement have been validated by a series of triaxial compression tests in which all of the three principal stresses play a role in the stress–strain–strength response. However, many geotechnical designs involve soil mass subjected to plane strain conditions. In this paper, laboratory plane strain compression tests were carried out with different heights of vertical inclusions along with horizontal reinforcement under four different confining stresses. In order to gain some insight into the driving micromechanics that govern the macroscale behaviour, the discrete-element method was used to model the behaviour of the reinforced soils and the modelling results were compared with the experimental results. The comparison showed that the predictions of the numerical analyses matched well with the experimental data in terms of macro-mechanical responses. Finally, it can be concluded from the analyses that a specified improvement in strength can be achieved using H–V inclusions compared with using only horizontal reinforcement.